2023
DOI: 10.5194/acp-23-10361-2023
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying SAGE II (1984–2005) and SAGE III/ISS (2017–2022) observations of smoke in the stratosphere

Larry W. Thomason,
Travis Knepp

Abstract: Abstract. Using a common analysis approach for data sets produced by the Stratospheric Aerosol and Gas Experiment instruments SAGE II and SAGE III/ISS, we identify 13 likely smoke events based on enhancements in the aerosol extinction coefficient. Nine of these are sufficiently large compared to ambient aerosol levels to compute mean mid-latitude 1020 nm optical depth enhancements that range from 0.0005 to 0.011. We also note that, for large events, the 525 to 1020 nm aerosol extinction coefficient ratio asymp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This is usually a very appropriate assumption, but significant exceptions can occur particularly following injections of smoke into the stratosphere or ash and, to a lesser extent, by the presence of organic aerosol or other non-absorbing, non-sulfuric acid aerosol. While several large smoke events have occurred over the past decade, they are a relatively minor component of the SAGE II aerosol record (Thomason and Knepp, 2023) and will not be considered further in this discussion though for some specific instances and for other instruments including the on-going SAGE III/ISS mission, composition cannot be as easily ignored. Using only WOPC data, we compute three sets of ratios (the SAD to 1020 nm extinction coefficient ratio (SADR), the VD to 1020 nm extinction coefficient ratio (VDR) and the 525 to 1020 nm extinction coefficient ratio (R)) in two altitude ranges (13 to 19.0 and 19.5 to 25 km) for the period where WOPC overlaps with the SAGE II mission.…”
Section: Variability Of Sad To Extinction Ratio As a Function Of Exti...mentioning
confidence: 99%
“…This is usually a very appropriate assumption, but significant exceptions can occur particularly following injections of smoke into the stratosphere or ash and, to a lesser extent, by the presence of organic aerosol or other non-absorbing, non-sulfuric acid aerosol. While several large smoke events have occurred over the past decade, they are a relatively minor component of the SAGE II aerosol record (Thomason and Knepp, 2023) and will not be considered further in this discussion though for some specific instances and for other instruments including the on-going SAGE III/ISS mission, composition cannot be as easily ignored. Using only WOPC data, we compute three sets of ratios (the SAD to 1020 nm extinction coefficient ratio (SADR), the VD to 1020 nm extinction coefficient ratio (VDR) and the 525 to 1020 nm extinction coefficient ratio (R)) in two altitude ranges (13 to 19.0 and 19.5 to 25 km) for the period where WOPC overlaps with the SAGE II mission.…”
Section: Variability Of Sad To Extinction Ratio As a Function Of Exti...mentioning
confidence: 99%
“…This observation is becoming more frequent in recent years (Zielinski et al, 2020). According to satellite-based studies of global extinction results wild fires can only be found in the lowermost part of the stratosphere with a relatively short lifetime (Thomason and Knepp, 2023). Therefore, the annual cycle with its natural variability and the origin of the Arctic stratospheric aerosol layer is important.…”
Section: Introductionmentioning
confidence: 99%